Pengaruh Fasilitas dan Promosi terhadap Kepuasan Pengunjung melalui Keputusan Berkunjung sebagai Variabel Intervening pada Objek Wisata Kota Semarang (Universitas Negeri Semarang, 2015)
The purpose of this study was to determine the influence of the facility and promotion of visitor satisfaction with the decision to visit as an intervening variable in Semarang city's attractions. The population in this study is a visitor attraction Semarang: Marine Tourism (Marina), Nature (Goa Kreo Gunung Pati), Religious Tourism (Sam Poo Kong temple), History (Lawang Sewu). The samples used in this study were 116 people by using accidental sampling with non-probability sampling approach. Methods of data collection using the questionnaire.Data analysis using regression analysis and path analysis. These results indicate that the facilities and the promotion directly affects customer satisfaction attractions of Semarang, the decision has been direct influence on satisfaction, facilities and promotion have an influence on satisfaction with the decision to visit as an intervening variable. Conclusions from this research is proven that a decision can be mediated effect visiting facilities and promotion of satisfaction.